View of the downtown skyline, 1962. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 12-30-62 p.A3. Oversize.
View of the downtown skyline, 1962. The photo was probably taken from the Winston-Salem Journal building on Marshall Street. The Nissen Building is at the right, with the Reynolds Building in the distance near left.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth